The Noodle Bowl Effect: Stumbling or Building Block? - Jong Woo Kang (Asian Development Bank (ADB), 2015)
Although it is well-known that a global trade regime best ensures economic welfare, there has nevertheless been a proliferation of free trade agreements (FTAs) between individual countries. This poses the challenge known as the "noodle bowl effect" - stemming from different rules of origins and technical standards. In this paper, we explore an economy's incentive for entering an FTA rather than anticipating a global trade regime. Using basic game theories, we show that in order for an equilibrium number of FTA participants to be obtained, the negative impact of FTAs should be significant. Globally, the side effects of FTAs centered on noodle bowl effects could contribute to inducing a global free trade regime - and also increase the viability of such regime once established. Ironically, then we need to encourage more FTAs across countries to facilitate the spread of greater noodle bowl effects instead of trying to curb the rush to FTAs to promote a global trade regime.
hdl:11540/5114
Keywords: C70; F10; F13; 330; FTA game; global trade regime; noodle bowl effect